Perspectives of Diabetes Mellitus Elderly and Care Givers on Quality of Life Related to Oral Health - วัฒนกูล, ศุทธินี; สิงห์คง, ณัฐหทัย; ตั้งยิ่งยง , น้ำเพชร (Journal of Health Science of Thailand, 2021)
The physical changes and chronic disease in elderly are directly associated with their quality of life. Diabetes mellitus (DM) affect the elderly’s quality of life especially slow down the healing process of oral diseases. The purposes of this qualitative study were to explore the perspectives of quality of life related to dental health status from DM Thai elderly and their care givers (CG). Data were collected by in-depth interviews and focus groups discussion from 4 districts selected by stratified random sampling from18 districts in Ubon Ratchathani, Thailand, in 2016. The samples were selected by purposive sampling, consisted of 16 DM elderly people who attended in-depth interviews, and 16 care givers from the same 4 districts who attended for focus group discussion. The Oral Impacts on Daily Performances Index (OIDP) was applied as guideline questions for the in-depth interviews and focus group discussion. Data were analyzed using content analysis by examine of transcriptions from audio recording and memory information. Data summary then classified and interpreted for research conclusions. The study showed that elderly’s and their care giver’s perspectives on quality of life were related to three dimensions of dental health conditions including physical, mental and social aspects. The DM elderly mostly reflected on the physical dimension. They stated that they wanted to feel tasty foods, proper chewing before swallowing and needed a denture if they lost any teeth. The reflection of mental dimension was about difficulty of sleeping when having toothache and gingivitis. Care giver’s perspectives were about pain management and decision making on choosing treatments or hospital for dental problems in DM elderly. This is the study of the diabetes mellitus elderly’s perspectives on quality of life related to dental health. The findings will therefore benefit the development of recommendations for consideration various factors that come into effect on dental health conditions in DM elderly. The findings would also be useful for the development of dental health promotion planning and activities to support the needs for oral health care and nutrition program for the DM elderly in order to improve their quality of life.